Introduction to International Ethical Standards Related to Genetics and Genomics - Seon-Hee Yim; Yeun-Jun Chung (Genomics & Informatics)
The rapid advances in genetic knowledge and technology raise various, sometimes unprecedented, ethical dilemmas in the scientific community as well as the public realm. To deal with these dilemmas, the international community has prepared and issued ethical standards in various formats. In this review, seven international standards regarding genetics and genomics will be briefly introduced in chronological order. Critical reflections on them will not be provided in this review, and naturally, they have their own problems and shortcomings. However, a common set of the principles expressed in them will be highlighted here, because they are still relevant, and many of them will be more relevant in the future. Some of the interesting contents will be selected and described. After that, the morality of one recent event related to whole-genome sequencing and person-identifiable genetic data will be explored based on those international standards.